SOCIAL RHETORIC IN THE ICONOGRAPHY OF SAINT NICHOLAS - Haładewicz-Grzelak, Małgorzata (Acta Neophilologica, 2011)
The societal presence of Saint Nicholas of Bari spans more than 15 centuries. Throughout this time, the persona of the bishop accumulated and carried changing values. This paper offers an exploratory tour through cultural temporalities. Along the coordinate of social rhetoric, the autho- ress analyses some aspects of power and bodily hexis. The study is conducted on the basis of a representative selection of the renditions of Saint Nicholas, which subsumes in total 350 pictures of devotional and religious representations (Western and Eastern Christianity), folk extensions and secular representations.